Adsorption Site Regulation to Guide Atomic Design of Ni–Ga Catalysts for Acetylene Semi‐Hydrogenation. (7th May 2020) - Cao, Yueqiang; Zhang, Hao; Ji, Shufang; Sui, Zhijun; Jiang, Zheng; Wang, Dingsheng; Zaera, Francisco; Zhou, Xinggui; Duan, Xuezhi; Li, Yadong
Abstract: Atomic regulation of metal catalysts has emerged as an intriguing yet challenging strategy to boost product selectivity. Here, we report a density functional theory‐guided atomic design strategy for the fabrication of a NiGa intermetallic catalyst with completely isolated Ni sites to optimize acetylene semi‐hydrogenation processes. Such Ni sites show not only preferential acetylene π‐adsorption, but also enhanced ethylene desorption. The characteristics of the Ni sites are confirmed by multiple characterization techniques, including aberration‐corrected high‐resolution scanning transmission electron microscopy and X‐ray absorption spectrometry measurements. The superior performance is also confirmed experimentally against a Ni5 Ga3 intermetallic catalyst with partially isolated Ni sites and against a Ni catalyst with multi‐atomic ensemble Ni sites. Accordingly, the NiGa intermetallic catalyst with the completely isolated Ni sites shows significantly enhanced selectivity to ethylene and suppressed coke formation. Abstract : Atomically regulating the Ni sites towards complete isolation by introducing Ga is theoretically predicted to lead to both preferential acetylene π‐adsorption and enhanced ethylene desorption. This concept is validated by experimental observations of the well‐designed NiGa intermetallic catalyst with completely isolated Ni sites for superior acetylene semi‐hydrogenation.